Ділова гра в аспекті міжпредметних зв’язків у навчанні іноземних мов у технічному університеті - Коломієць, Світлана Семенівна; Kolomiyets, S. S. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Мета статті – розмежувати поняття «рольова гра», «рольова професійно орієнтована гра» і «ділова гра» та розглянути ділову гру в аспекті міжпредметних зв’язків. Проаналізовано трактування зазначених понять вітчизняними та зарубіжніми авторами, розглянуто питання організації та проведення ділової гри в технічному університеті як форми реалізації міжпредметної взаємодії мовної та фахової кафедр, проаналізовано понятя рольової професійно орієнтованої та ділової гри, схарактеризовано їх спільні риси і розбіжності. Подано тлу¬мачення міжпредметних зв’язків, розглянуто їхні рівні, особливу увагу приділено функціям та типізації міждисциплінарної взаємодії. При цьому увага фокусується на встановленні взаємозв’язків між рівнем між¬пред¬метної взаємодії та різновиду рольової гри. Уміщено аналіз результату ділової гри з погляду формування іншомовної комунікативної компетентності та фахової компетенції. Подано визначення ділової гри як форми міжпредметної взаємодії. The article deals with the problem of interactive teaching foreign languages in accordance with interdisciplinary links at technical universities. Represented article justifies the necessity of distinguishing the notions of role-play, specialism-related role play and business game. Role play as the form of interactive teaching is considered, the focus being on distinguishing specialism-related role games and business games in terms of interdisciplinary teaching. Their common and different features are studied. Interdisciplinary approach to teaching foreign languages is analyzed. The notion of interdisciplinary links in teaching, their functions, levels and types are considered. The relations between the type of a game and the level of interdisciplinary links are specified, business game being treated as a form of interdisciplinary cooperation between language and specialism departments. The article presents distinguishing characteristics of specialism-oriented role plays and business games in terms of the level of interdisciplinary links. Their peculiarities resulting from different levels of interdisciplinary interaction are outlined. The author’s definitions of role specialism-related game and business game are given. The scheme of interaction between teachers and students in business game is presented.
Business Game in Terms of Interdisciplinary Links in Teaching Foreign Languages at Technical Universities
Keywords: рольова гра; role-play; рольова професійно орієнтована гра; specialism-oriented role play; ділова гра; business game